Foreshock compressional boundaries observed by Cluster. Issue 2 (12th February 2013) - Rojas‐Castillo, D.; Blanco‐Cano, X.; Kajdič, P.; Omidi, N.
Abstract : [1] Recent global hybrid simulations (kinetic ions, fluid electrons) of the solar wind interaction with Earth's magnetosphere revealed the existence of a new structure at the edges of the foreshock, named foreshock compressional boundary (FCB). The FCB is associated with a strong compression of magnetic field magnitude and density followed by strong decreases of these two quantities. This structure represents a transition region that separates the highly disturbed foreshock plasma from the solar wind. Hybrid simulations have shown that the formation and strength of the FCB depend on the generation and nonlinear evolution of ultra‐low frequency (ULF) waves which in turn have been produced by the interaction of foreshock backstreaming ions with the solar wind. In this work, we use Cluster magnetic field and plasma data to show that the FCB exists and is frequently observed in the foreshock region. We study FCB properties during 36 crossings for different interplanetary field geometries and solar wind speeds. The results presented here reveal that FCBs form for different solar wind conditions (i.e., cone angle, velocity), and are highly nonlinear structures with δB / B o and δn / n o amplitudes around 40% of the ambient values. We find that the FCB is sometimes a transition region between the pristine solar wind plasma and the foreshock plasma. At other times, it separates a region with large amplitude waves from regions with high frequency small amplitude waves. Preliminary analysis of ion distributions show that in some cases the FCB can coincide with the ULF wave boundary and in others with the intermediate ion boundary. Cluster data also show that the solar wind flow is decelerated and deviated when crossing the FCB. Key Points: We show first observational evidence of foreshock compressive boundary Study the properties of foreshock compressive boundaries Foreshock compressive boundaries are compressive structures